GARAP EKSPRESI TEMBANG DAN ANTAWECANA WAYANG BOCAH SAMPARAN SAMPIRANKU - Chikal Safa Nandhita; Nandhang Wisnu Pamenang; Budi Setyastuti; Karyono (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2023)
Tembang and antawecana are one of the components of dance which is called the verbal component. These components can be enjoyed through language, speech and the intonation of a sentence. Cultivating the verbal component can influence the results of the expression produced based on the delivery of the verbal component through the intonation of the song and the emphasis of the words in the antawecana. Strengthening the expressions of wayang orang or wayang anak players can be accompanied by tembang and antawecana. It depends on the accuracy of tembang and antawecana used and placed in the right position. The existence and choice of place is also an asset in finding the desired expression for a wayang orang artist. Wayang orang Samparan Sampiranku is one of the children's wayang works that uses songs and antawecana as a form of expression in communicating and conveying emotions. This research emphasizes descriptive analysis carried out to find an analysis of the expressions obtained based on the description of the songs and antawecana contained in the Wayang Bocah work entitled Samparan Sampiranku presented by Sanggar Sarwi Retno Budoyo in 2022 at the Wayang Bocah Festival. Keywords: Tembang, Antawecana, Garap, Expression